VD_FINDINFO Pron / 2014 / 26 vom 28. Mai 2014 - VD Tribunal cantonal (2014)
MODÉRATION, HONORAIRES CALCULÉS EN FONCTION DU RÉSULTAT POSITIF, HONORAIRES, AVOCAT | 45 al. 1 LPAv, 45 LPAv, 50 al. 3 LPAv, 50 LPAv